Factors Affecting Solid Waste Management Behaviours of Households in Thap Sakae District, Prachuap Khiri Khan Province - Ninsook, Aphinat; Benjakul, Sarunya; Kengganpanich, Mondha (Journal of Behavioral Science for Development, 2022)
The correlational research aimed to describe the factors affecting solid waste management of the household. The samples were 403 representatives of households and living in Thap Sakae district, Prachauap Khiri Khan Province over 6 months. The theory of planned behavior (TPB) was applied as a research conceptual framework by using the questionnaire. Descriptive statistics and inferential statistics composing Chi-square test, Pearson correlation and Multiple regression analysis were used to analyze data. The results revealed that most sample had improper solid waste Management behaviours (67.7%). Three factors were statistically significantly related to solid waste management behaviors, composing of subjective norms (r = .171, p < .001), perceived behavior control (r = .281, p < .001), and behavioral intention (r = .248, p < .001). The results of the multiple regression analysis composing of behavioral intention (β = .301, p < .001), and perceived behavioral control (β = .282, p < .001). These two factors could statistically predict solid waste management behaviors up to 27.0 % (Nagelkerke R2 = .27) Therefore, officers of sub district administrative organization or sub district municipality, communities, and various sectors should collaborate to organize activities in regard to solid waste management. These activities will increase the confidence and skills, and will not be seem as obstructing the management of solid waste at the source.